Economic Impacts of SECA Regulation on Maritime Companies in the Baltic Sea Region – Literature Review and Low Emissions Recommendations: Part 1 - Esa Hämäläinen; Tommi Inkinen (Serbia, 2022)
The Intergovernmental Panel on Climate Change (IPCC) has stated that climate change is a major ongoing process requiring strict restrictive actions on a global level. This paper focuses on literature covering the impacts of the Sulphur Emission Control Area (SECA) based on academic papers published in 2017–2018. In numerous studies conducted before 2015, it was predicted that regulation would have serious impacts on maritime businesses. This is the first part of our research introducing the topic. The paper continuous in Part 2.
Proceedings of the 4th Logistics International Conference